2014
DOI: 10.1063/1.4896121
|View full text |Cite
|
Sign up to set email alerts
|

Real-time magnetic nanothermometry: The use of magnetization of magnetic nanoparticles assessed under low frequency triangle-wave magnetic fields

Abstract: In this study, we propose and demonstrate the usefulness of employing time-varying magnetization of a magnetic nanoparticle (MNP) based sample, induced by low frequency (f = 25 Hz) triangular-wave magnetic field, to achieve the approach of real-time recording of magnetization curve, which allows precise and noninvasive temperature probing with real-time performance. Moreover, the present report introduces the design and performed the test of a detection system for accurate and real-time recording of the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…7) represent the dependence of temperature probing accuracy with respect to the response time. Indeed, we found that the increase in the response time improves the temperature probing accuracy, in good agreement with our recent report [20]. This finding is of great importance to the application of magnetic nanothermometry.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…7) represent the dependence of temperature probing accuracy with respect to the response time. Indeed, we found that the increase in the response time improves the temperature probing accuracy, in good agreement with our recent report [20]. This finding is of great importance to the application of magnetic nanothermometry.…”
Section: Resultssupporting
confidence: 89%
“…2) are calculated by the digital phase-sensitive detector (DPSD) algorithm. The MNP magnetization is temperature dependent no matter how complex the particle-particle interaction and the particle size distribution are, and therefore, it has been proved theoretically and experimentally to provide the background for magnetic nanothermometry [16]- [20]. Fig.…”
Section: Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can therefore represent a first step toward real-time and accurate heat quantification in vivo, which is an essential step toward implementation of magnetic hyperthermia in clinic. 36,37 Nowadays, the most commonly used and reliable systems for probing the heat of SPIONs are fiber optic cables, which can record information from the colloidal suspension. However, the results are dependent on the spatial position of the temperature sensor.…”
Section: Introductionmentioning
confidence: 99%